Three dimensional (3D) navigation of Universiti Malaysia Pahang (Pekan) - Satish Kumar, Raja Mohan (2014)
In this globalization era buildings are being piled up all over the places and routes are being adjusted in order that people can pass through the new buildings. However, people take times to discover the routes. This is where the navigation becomes helpful for the people to find their way to their destination. For example, Universiti Malaysia Pahang campus Pekan has been added with some new buildings recently and intakes also being increasing every year. Thus new intake can't seem to find their way around at first. Giving them a three dimensional (3D) feel of the environment through the navigation system would be a good exposure. The 3D navigation would also represent the university as a technology university. This 3D navigation also gives a surround look at the destination together with audio input. This system also gives the choices of vehicle and estimation time taken to reach the destination. The objective this system is to help the students navigate through the system especially the new intakes together with their parents. System Development Life Cycle (SDLC) is the method that was chosen to develop the system. This method consists of five phases which are planning, analysis, design and development, implementation and testing. This methodology is chosen because it attempts to reduce inherent project risk by breaking a project into smaller segments, provides easy to change during the development process and it is suitable used on developing this system. The 3D navigation is a web based system and Adobe Dreamweaver is used to create the interface of the system and Maya will be used to create the 3D modelling. This 3D navigation is expected to give the students ease on navigating through the university.